A generic model for vocationally oriented public relations education in globalised contexts - Elizabeth Ferreira (Communicare)
This article reports on a prescriptive generic Globalisation Model that was developed for vocationally oriented public relations education in globalised contexts. The model is based on a literature study that pointed out that the public relations profession is both affected by the forces of globalisation, and it has the potential to play a role in the management of globalisation towards a constructive outcome. The model consists of a recommended curriculum and recommendations pertaining to the functioning of public relations education departments in the context of globalisation. It is accompanied by an annexure indicating how the generic Globalisation Model should be adapted for application in South Africa.